Anteseden dan konsekuen strategi lingkungan proaktif pada perusahaan di Indonesia - Arini Lukita Ismiranti; Amin Wibowo (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2018)
Since the agreements of Environmental Sustainability Development (ESD) was initiated, environment issue has become an essential concern for daily business activities. This leads corporates to implement environmental strategy, especially in the proactive manner. The aim of this study is to investigate the effect of institutional pressures on proactive environmental practices and to examine the implication of proactive strategy to the corporate reputation. Using survey data from 76 companies in Indonesia, multiple regression analysis showed that pressure from competitors and professional networks positively influenced proactive strategies, while regulatory pressure did not influence proactive strategies. Our evidence implied that external factors from competitors and professional networks pressures were important driving forces for corporates to apply proactive strategies. In addition, this study found a positive influence of proactive strategy on corporate reputation.